2017
DOI: 10.1007/s12185-017-2282-5
|View full text |Cite
|
Sign up to set email alerts
|

Administration of direct oral anticoagulants in patients with myeloproliferative neoplasms

Abstract: Direct oral anticoagulants (DOACs) have been approved to treat and prevent thrombotic events. However, they are not yet labeled for use in patients with active cancers. Myeloproliferative neoplasms (MPNs) are clonal chronic disorders with a high incidence of thrombotic events, for which low-dose aspirin (LDA) is the standard drug treatment. We analyzed efficacy and safety of DOACs prescription in patients treated for MPNs. An MPN database, the OBENE registry, was established at our institution. We collected bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 14 publications
3
67
2
1
Order By: Relevance
“…In conclusion, our results from a small cohort study showed that in those with MPN and previous VTE, the use of DOACs was associated with very low/no recurrence rates of VTE and no major bleeding complications. These data are in line with the currently limited literature whereby studies demonstrate the efficacy and safety of DOACs, with a reduction in recurrence rates of thrombosis (Ianotto et al , ; De Stefano et al , ). Our data show that those with unusual sites of VTE, including splanchnic vein thromboses and cerebral venous sinus thrombosis, had no recurrent VTE with the use of DOACs.…”
Section: Clinical Characteristicssupporting
confidence: 88%
“…In conclusion, our results from a small cohort study showed that in those with MPN and previous VTE, the use of DOACs was associated with very low/no recurrence rates of VTE and no major bleeding complications. These data are in line with the currently limited literature whereby studies demonstrate the efficacy and safety of DOACs, with a reduction in recurrence rates of thrombosis (Ianotto et al , ; De Stefano et al , ). Our data show that those with unusual sites of VTE, including splanchnic vein thromboses and cerebral venous sinus thrombosis, had no recurrent VTE with the use of DOACs.…”
Section: Clinical Characteristicssupporting
confidence: 88%
“…Direct oral anticoagulants (DOACs) are increasingly used in the non‐MPN population for prophylaxis and VTE therapy. However, there is limited data for their specific use in MPN, where they appear to be safe and efficacious (Ianotto et al , ).…”
Section: Management Of Specific Situations In Polycythaemia Veramentioning
confidence: 99%
“…The management of pruritus is challenging. Symptoms can improve or resolve with control of blood counts, using venesection alone or with cytoreductive therapy (Le Gall- Ianotto et al, 2017). Improvement in pruritus has been reported with hydroxycarbamide (Sharon et al, 1986), interferon (although this drug can also worsen pruritus) (Lengfelder et al, 2000), busulfan and 32 P (Jackson et al, 1987).…”
Section: Recommendations: Pregnancy Managementmentioning
confidence: 99%
“…The evidence on use of DOACs in MPN is limited to small number of patients (25 patients) where they appear to be safe and efficacious. 31 Therefore, use of these anticoagulants should be considered only in case-by-case basis by assessing the risk of bleeding versus thrombosis (►Fig. 2).…”
Section: Management Of Acute Thrombosis and Subsequent Management At mentioning
confidence: 99%